A comparative study of the Physical Fitness Performance of UPV-CAS Entering Freshmen students from school year 1981 to 1986 - Drilon, Erlinda
This study was concerned with the physical fitness performance f entering freshmen in UPV-CAS from school year 1981 to 186 in seven test items of the ICSPFT Battery tests. Its objectives were: 1) To determine the average actual performance of entering freshmen in UPV_CAS for school year 1981 to 1986 in seven test items of the ICSPFT Battery tests 2) To compare the results of the physical fitness performance of entering freshmen between each year 3) To compare the average results of the physical fitness performance of entering UPV-CAS freshmen from school year 1981 to 1986 with the Philippine norm in only four test items. The research utilized the descriptive and statistical method. The statistical analysis of data made use of mean. The Philippine mean score was sed to compare the results of UPV-CAS performance score. The four major phases in the procedure were as follows: 1) The identification of the test population and the orientation of the ICSPFT Battery test to the test population 2) Collection, analysis, and interpretation of data gathered 3) The determination of the UPV-CAS mean scores in the physical fitness performance test 4) drawing of findings, conclusions and recommendations to enrich and improve the physical education curriculum in UPV-CAS. The instrument utilized to obtain measures of physical fitness was the ICSPFT Physical Performance Battery test. This elicited information related to speed, leg power, agility, arm-shoulder strength and endurance, cardio-respiratory endurance, flexibility, and abdominal strength and endurance. The subjects for this study was the 1,003 incoming freshmen students of UPV-CAS actually enrolled in the first semester from school year 1981 to. 1986. Based on the results of this study the following conclusions and recommendations are given: In general, UPV-CAS entering female freshmen from school year 1981 to 1986 have more or less similar measures of agility, speed and abdominal strength and endurance, but in other items of fitness components namely; flexibility, leg power, arm-shoulder strength and endurance, and cardio-respiratory endurance performance measures differ quite significantly between each year. Thus, 1981-82 female students have greater leg power; 1982-83 are flexible, have stronger abdominal strength and endurance but weak in leg power; 1983-84 are poor in flexibility; 1984-85 are poor in arm-shoulder strength and endurance; and 1985-86 have better speed performance, best in arm-shoulder strength and endurance but poor in cardio-respiratory endurance. On the other hand, male UPV-CAS entering freshmen for school year 1981-82 have greater arm-shoulder strength and endurance but poor in leg-power; 1982-83 posses cardio-respiratory endurance; 1983-84 have greater leg power; 1984-85 like the 1983-84 have also greater leg power but poor in arm-shoulder strength and endurance. In general, UPV-CAS entering male freshman from school year 1983-84 performed better than the rest of the years in almost all test items of the ICSPFT battery test namely: leg power, abdominal strength and endurance, speed flexibility, and agility. With regard to the comparison of the average physical fitness performance scores of UPV-CAS entering freshmen and the Philippine mean in four test items the result showed that the UPV-CAS entering female freshmen have better physical fitness performance in leg power and abdominal strength and endurance than the Philippine female student however, in the items of agility and speed both have the same performance. On the other hand male students have better performance in abdominal strength and endurance and posses speed than the UPV-CAS male freshmen, however, UPV-CAS male students have stronger leg power and are agile. Based on the conclusions the following recommendations are presented: 1) UPV-CAS entering female freshmen for school year 1981 to 1986 should be encouraged to improve their physical fitness performance on the following physical fitness components namely; flexibility, leg power, abdominal strength and endurance and cardio-respiratory endurance by engaging in more activities geared toward the development of such deficiencies. For flexibility bending, stretching and twisting exercises are recommended; jogging, walking, running, leg kicking and leg lifting for leg power; sit ups, sitting kicks, leg lift and other stretching and contractions for abdominal strength and endurance; and for the cardio-respiratory endurance, running in place, jogging, rope skipping, bicycling and swimming are highly recommended. 2) UPC-CAS entering male freshmen should likewise be encouraged to develop their leg power, abdominal strength and endurance and arm-shoulder strength and endurance. For arm-shoulder strength and endurance, hand stand, push ups and pulls ups exercises are recommended for such deficiencies. 3) More physical fitness exercises in the Physical Education classes be geared toward regular performance of physical fitness activities for the development of flexibility, leg power, abdominal strength and endurance, and cardio-respiratory endurance among females and arm-shoulder strength and endurance and speed among males. In view of this P.E. facilities and equipment and other testing facilities and equipment like video, betamax, etc. be provided for follow-up study in order to attain better results. a follow up study on the physical fitness performance of incoming freshmen in UPV-CAS be conducted for the next five years to serve as basis for curricular projections of the Physical Education Department. 5) A similar study should be conducted among elementary and high school levels both in public and private schools and universities in order to establish a baseline data of the physical fitness performance of students in elementary and secondary levels.
Final Report (Physical Education Department). -- [Iloilo City] : UPV-CAS, [n.d.]